Gene Signatures Distinguish Stage‐Specific Prostate Cancer Stem Cells Isolated From Transgenic Adenocarcinoma of the Mouse Prostate Lesions and Predict the Malignancy of Human Tumors. (24th July 2013) - Mazzoleni, Stefania; Jachetti, Elena; Morosini, Sara; Grioni, Matteo; Piras, Ignazio Stefano; Pala, Mauro; Bulfone, Alessandro; Freschi, Massimo; Bellone, Matteo; Galli, Rossella
Abstract : This study established long‐term self‐renewing prostate cancer stem cell (PCSC) lines from the different stages of transgenic adenocarcinoma of the mouse prostate (TRAMP) progression by application of the neurosphere assay. It was found that TRAMP‐derived PCSCs represent a novel and valuable preclinical model for elucidating the pathogenetic mechanisms leading to prostate adenocarcinoma and for the identification of molecular mediators to be pursued as therapeutic targets. Abstract : The relevant social and economic impact of prostate adenocarcinoma, one of the leading causes of death in men, urges critical improvements in knowledge of the pathogenesis and cure of this disease. These can also be achieved by implementing in vitro and in vivo preclinical models by taking advantage of prostate cancer stem cells (PCSCs). The best‐characterized mouse model of prostate cancer is the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. TRAMP mice develop a progressive lesion called prostatic intraepithelial neoplasia that evolves into adenocarcinoma (AD) between 24 and 30 weeks of age. ADs often metastasize to lymph nodes, lung, bones, and kidneys. Eventually, approximately 5% of the mice develop an androgen‐independent neuroendocrine adenocarcinoma. Here we report the establishment of long‐term self‐renewing PCSC lines from the different stages of TRAMP progression by application of the neurosphere assay. Stage‐specific prostate cell lines were endowed with the critical features expected from malignant bona fide cancer stem cells, namely, self‐renewal, multipotency, and tumorigenicity. Notably, transcriptome analysis of stage‐specific PCSCs resulted in the generation of well‐defined, meaningful gene signatures, which identify distinct stages of human tumor progression. As such, TRAMP‐derived PCSCs represent a novel and valuable preclinical model for elucidating the pathogenetic mechanisms leading to prostate adenocarcinoma and for the identification of molecular mediators to be pursued as therapeutic targets.